Experimental study of a new low reflection breakwater - C.-S. Ciocan (2015)
Perforated-wall vertical structures are becoming more and more popular, not only as external caisson breakwaters, but also as lower reflective quay walls, in areas where the use of rubble-mound breakwaters and gentle slopes within the harbour basin are unfeasible due to space limitations or physical, economical or technical constraints. This paper presents the preliminary structural and hydraulic design using the Goda method and the physical model testing of a novel concept, the LOWREB structure, carried out to analyse the hydraulic efficiency with respect to reflection for varying wave conditions and structure geometries. (c) 2016 Taylor & Francis Group, London.